Memes and Interactivity of Facebook Mobile Legends Gamers After the Fall of RRQ - Dwi Prasetyo Yulianto; Moch Fuad Nasvian; Dimas Rifqi Novica (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
This research aims to determine the level of interactivity in meme postings by netizens during the M4 World Tournament of the game Mobile Legends: Bang Bang (MLBB). Utilizing the Facebook platform, specifically the